LEGAL PROTECTION AGAINST THE CASE OF PT. MOTTOLEDO AS A VIOLATOR OF FEN LIE PATENT RIGHTS - Putu Reza Aditya Tirandika; Made Gde Subha Karma Resen (Transpublika Publisher, 2023)
Intellectual property rights (IPR) pertain to property rights derived from human intellectual capabilities, encompassing various forms of talent displayed in technology, science, art, and literature. Adequate legal protection is essential for intellectual works to nurture societal creativity and ensure successful safeguarding of intellectual property rights. This study aims to assess the legal protection of intellectual property rights against PT Mottoledo Fen Lie Agen as a patent infringer. This study employs a normative legal study approach, focusing on the positive legal norms governing the protection of intellectual property rights against PT Mottoledo Fen Lie Agent's patent infringement. The study identifies the substantive requirements for patentability of an invention, namely: novelty, inventive steps, and industrial applicability, as specified in Articles 2-5 of the Patent Law. Concerning copyrighted books and similar works, the protection system discussed earlier adopts an automatic approach. This means that creators do not need to undergo a registration process to obtain legal protection; protection automatically exists from the moment the copyrighted work is created as a tangible expression, such as a copyrighted book, etc.